2014
DOI: 10.1089/dna.2013.2270
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms in theESR1Gene and Cerebral Infarction Risk: A Meta-Analysis

Abstract: A number of studies have documented that estrogen receptor α (ESR1) may play an important role in the development and progression of cerebral infarction, but many existing studies have yielded inconclusive results. This meta-analysis was performed to evaluate the relationships between ESR1 genetic polymorphisms and cerebral infarction risk. The PubMed, CISCOM, CINAHL, Web of Science, Google Scholar, EBSCO, Cochrane Library, and CBM databases were searched for relevant articles published before October 1, 2013,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…The female reproductive hormone estrogen is also well known to affect cardiovascular functions, such as maintenance of lipid profile, anti-atherosclerotic and anti-inflammatory action, increasing vasodilation, enhancing HDL levels, attenuation of cardiac cell apoptosis [ 3 , 4 ] and modulation of insulin secretion [ 5 ]. The hormone binds with a ligand activated transcription factor, estrogen receptor alpha (ERα) encoded by ESR1 gene and influences several physiological and cellular processes.…”
Section: Introductionmentioning
confidence: 99%
“…The female reproductive hormone estrogen is also well known to affect cardiovascular functions, such as maintenance of lipid profile, anti-atherosclerotic and anti-inflammatory action, increasing vasodilation, enhancing HDL levels, attenuation of cardiac cell apoptosis [ 3 , 4 ] and modulation of insulin secretion [ 5 ]. The hormone binds with a ligand activated transcription factor, estrogen receptor alpha (ERα) encoded by ESR1 gene and influences several physiological and cellular processes.…”
Section: Introductionmentioning
confidence: 99%
“…ESR1 is mainly expressed in macrophages, endothelial cells, and vascular smooth muscle cells, and it plays an important role in vascular wall physiology and function (Gao et al, 2014). The ESR1 gene, spanning approximately 25 kb, is located on chromosome 6q21 and consists of 16 exons (Drayna et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Many neuroprotective agents can enhance Akt activity and protect brain injury, indicating that AKT is the main mechanism of cell repair after injury 58 . Gao’s findings have indicated that ESR1 genetic polymorphisms may contribute to the development of cerebral infarction, especially in the female population 59 ]. A recent study found that stroke was significantly associated with ESR1 rs2234693 polymorphism, especially ischemic stroke 60 .…”
Section: Discussionmentioning
confidence: 99%